Exogenous Application of Proline and L-Cysteine Alleviates Internal Browning and Maintains Eating Quality of Cold Stored Flat ‘Maleki’ Peach Fruits - Gholamreza Gohari (MDPI AG, 2021)
The postharvest life of flat peach fruit is limited by the appearance of chilling injury symptoms, especially internal browning. In this study, impacts of the exogenous application of proline (0, 5, 10, and 15 mM) and L-cysteine (0, 0.2, 0.4 and 0.6%) on attenuating chilling injury of flat peach fruit were evaluated all over the cold storage. The results demonstrated that the fruits treated with 15 mM proline and 0.4 % L-cysteine showed lower levels of internal browning and these treatments prevented the excess enhancement of total soluble solids (TSS), the decline of titratable acidity (TA) content and the loss of fruit firmness during storage time. A lower accumulation of hydrogen peroxide (H2O2), malondialdehyde (MDA), electrolyte leakage, and higher activity of antioxidant enzymes, along with higher ascorbic acid content and antioxidant capacity, were observed in treated fruits. Treated fruits also showed higher activity of phenylalanine ammonia lyase (PAL) and conversely lower activity of polyphenol oxidase (PPO), which led to a higher accumulation of total phenols and flavonoids. Moreover, a higher accumulation of endogenous proline was observed in 15 mM proline treated fruits. Eventually, according to our results, the exogenous administration of proline and L-cysteine as safe, natural and environmentally friendly treatments, preserved the nutritional quality of flat peach fruits during long-term cold storage.